FAKTOR-FAKTOR YANG MEMENGARUHI NILAI PERUSAHAAN DENGAN MODERASI CORPORATE SOCIAL RESPONSIBILITY - Defianti Hermawan; Sofia Prima Dewi (Jurnal Paradigma Akuntansi, 2023)
The purpose of this study is to examine the effect of financial performance, managerial ownership, and board of independent commissioners on firm value by using corporate social responsibility as moderating variable. This study uses 168 data samples from manufacturing companies listed in Indonesia Stock Exchange during the period of 2017-2020 and Eviews 12 for data processing. The result of this study show that financial performance have positive effect on firm value, managerial ownership have negative effect on firm value, and board of independent commissioners have positive and no effect on firm value. In addition, corporate social responsibility is able to moderate the relationship between financial performance and managerial ownership on firm value while it can not moderate the relationship between board of independent commissioners on firm value.